PENGARUH KEKERASAN PADA CYBERBULLYING TERHADAP PERILAKU MASYARAKAT PADA MASA COVID-19: Indonesia - Ricky Andi Kurniawan; Kelvin; Kevin Anderson; Djayadhinata; Olwin; Indra Saputra (Universitas Majalengka, 2022)
The purpose of this study was to determine the condition of cyberbullying that happened the city of Batam, especially during the ongoing Covid-19 pandemic. The types of research we use are qualitative and quantitative. This research was conducted with many respondents with a total of 250 respondents. The sampling technique used is the Cluster & Stratified Random Sampling technique. The results showed that 30.8% often experienced or encountered cases of Cyberbullying and 45.2% had experienced or encountered cases of Cyberbullying. From the research, 62.8% experienced it in the school environment and 37.2% experienced it outside the school environment. This research can be a reference for readers in finding and determining the level of Cyberbullying cases in Batam city and how to handle them.